2020
DOI: 10.35741/issn.0258-2724.55.3.30
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Transformation of New City Area: Economic, Social, and Environmental Sustainability Perspective of Makassar City, Indonesia

Abstract: The spatial transformation of new urban areas into industrial urban areas impacts spatial structure, spatial patterns, and environmental degradation. This study aims to analyze the spatial transformation work as a determinant of the development of the new urban area of Metro Tanjung Bunga Makassar and analyze the relationship of spatial expansion, land use change and population increase for the growth of new city areas and the sustainable development of the Metro Tanjung Bunga area, Makassar city. The data for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Thus, it can be concluded that SMEs in Makassar City still need guidance and assistance to increase the productivity and stability of economic enterprises in a sustainable manner. It is, therefore, necessary to increase support for SMEs, including in financial management, production, business management, and market access [149]. Furthermore, missions, visions, and strategies are very important in supporting SME economic enterprises to maintain business sustainability in the long term [150].…”
Section: Human Resource Capacity and Business Sustainability Of Smesmentioning
confidence: 99%
“…Thus, it can be concluded that SMEs in Makassar City still need guidance and assistance to increase the productivity and stability of economic enterprises in a sustainable manner. It is, therefore, necessary to increase support for SMEs, including in financial management, production, business management, and market access [149]. Furthermore, missions, visions, and strategies are very important in supporting SME economic enterprises to maintain business sustainability in the long term [150].…”
Section: Human Resource Capacity and Business Sustainability Of Smesmentioning
confidence: 99%
“…Scientists have argued that using peat as an energy source on a large scale, comparable to using fossil hydrocarbons, nuclear power, or hydropower, is hardly possible for many economic and environmental reasons. It applies even to countries with impressive peatlands, peat resources, and growth, on both a per unit area and per capita basis (Lempinen, 2019;Mugerwa et al, 2019;Surya et al, 2020). With the discovery and development of large fossil hydrocarbon deposits, the development of nuclear power, and large-scale hydropower, the competitiveness of peat as a fuel has decreased (Pakere & Blumberga, 2017;Semin et al, 2019a;Progunova et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…[11] In spite of the investment opportunities presented by the governments are closely linked to the economic engine in urban areas and cities, However, providing the most significant ability to interact between different actors and organizations in creating useful solutions to activate parts of the city is most important. [12] This interaction depends on the quality of the partnership between the two parties and determines the priorities for participation in forming the new areas of the city.…”
Section: Urban Development Activitiesmentioning
confidence: 99%